Genome and evolution of the arbuscular mycorrhizal fungus Diversispora epigaea (formerly Glomus versiforme) and its bacterial endosymbionts. Issue 3 (13th October 2018) - Sun, Xuepeng; Chen, Wenbo; Ivanov, Sergey; MacLean, Allyson M.; Wight, Haley; Ramaraj, Thiruvarangan; Mudge, Joann; Harrison, Maria J.; Fei, Zhangjun
Summary: Arbuscular mycorrhizal (AM) fungi form endosymbioses with most plants, and they themselves are hosts for Mollicutes/ Mycoplasma ‐related endobacteria (MRE). Despite their significance, genomic information for AM fungi and their MRE are relatively sparse, which hinders our understanding of their biology and evolution. We assembled the genomes of the AM fungus Diversispora epigaea (formerly Glomus versiforme ) and its MRE and performed comparative genomics and evolutionary analyses. The D. epigaea genome showed a pattern of substantial gene duplication and differential evolution of gene families, including glycosyltransferase family 25, whose activities are exclusively lipopolysaccharide biosynthesis. Genes acquired by horizontal transfer from bacteria possibly function in defense against foreign DNA or viruses. The MRE population was diverse, with multiple genomes displaying characteristics of differential evolution and encoding many MRE‐specific genes as well as genes of AM fungal origin. Gene family expansion in D. epigaea may enhance adaptation to both external and internal environments, such as expansion of kinases for signal transduction upon external stimuli and expansion of nucleoside salvage pathway genes potentially for competition with MRE, whose genomes lack purine and pyrimidine biosynthetic pathways. Collectively, this metagenome provides high‐quality references and begins to reveal the diversity within AM fungi and their MRE.